A Comparison of BHP-Billiton’s Minera Escondida Flotation Concentrators - H. E. Urtubia (Canadian Institute of Mining, Metallurgy and Petroleum, 2006)
"BHP-Billiton’s Minera Escondida Limitada, in Chile, is one of the world’s largest copper producers. It treats a combined 10,500 tph of copper ore through its two concentrators: Los Colorados and Laguna Seca. The performance of the rougher circuit at each concentrator was measured and analysed using the JKTech flotation optimisation methodology. This involved developing a flotation model for each concentrator based on cell operating parameters (for example bubble surface area flux and froth recovery) and feed ore floatability characteristics. The rougher circuit performance was evaluated in terms of traditional measures, such as grade and recovery. The operation was also analysed using the measured cell operating parameters and ore floatability and the effect of these with regard to performance (grade / recovery) was assessed.This paper presents a comparison of the rougher circuit at each concentrator in terms of these parameters. The main differences in rougher circuit performance between the two plants were attributed to differences in feed ore floatability characteristics and froth recovery. The comparison highlighted opportunities where performance improvements could be made. The study also showed the usefulness of separating the flotation process into easily measurable subprocesses to further identify the different mechanisms occurring in each rougher circuit. Traditional measures like grade and recovery are useful for monitoring flotation operation but this data lacks the depth to determine the root cause behind operational issues. Determining the operating parameters and ore floatability provides the operating plant metallurgist better tools to assess and manage these issues."